Academic Resilience as Predictor of Secondary School Students' Academic Achievement in Biology in Ogidi Education Zone - Nnoli, Juliana Nkiru; Mbaegbu, Chioma S.; Achebe, Chinecherem Miracle (Education and Development Research, 2026)
The study investigated academic resilience as a predictor of secondary school students’ academic achievement in Biology in Ogidi Education Zone, Anambra State. A correlational survey research design was adopted for the study. The population comprised all Senior Secondary Two (SS2) students offering Biology in government-owned schools in the zone. A sample of 348 students (165 males and 183 females) was drawn using a multistage sampling technique. The instruments used for data collection were the modified Simon Cassidy Academic Resilience Scale (ARS-30) and the students’ cumulative annual Biology results for the 2024/2025 academic year. The Academic Resilience Scale was validated by three experts from the Faculty of Education, Nnamdi Azikiwe University, Awka. The reliability of the instrument was established using the Cronbach's Alpha method, which yielded a coefficient of 0.82. Data collected was analyzed using regression analysis at the 0.05 level of significance. The findings of the study revealed that academic resilience significantly and positively predicted students’ academic achievement in Biology. The study also revealed that gender did not significantly moderate this relationship. It was recommended among others that schools should integrate resilience-building into teaching, counseling, and school programs to enhance students’ academic achievement in Biology.